2009
DOI: 10.1128/jb.01166-08
|View full text |Cite
|
Sign up to set email alerts
|

Geobacter sulfurreducens Contains Separate C- and A-Adding tRNA Nucleotidyltransferases and a Poly(A) Polymerase

Abstract: The genome of Geobacter sulfurreducens contains three genes whose sequences are quite similar to sequences encoding known members of an RNA nucleotidyltransferase superfamily that includes tRNA nucleotidyltransferases and poly(A) polymerases. Reverse transcription-PCR using G. sulfurreducens total RNA demonstrated that the genes encoding these three proteins are transcribed. These genes, encoding proteins designated NTSFI, NTSFII, and NTSFIII, were cloned and overexpressed in Escherichia coli. The correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In organelles, the tRNA nucleotidyltransferase only has to add two nucleotides, C and A, to the 39 end because a high number of plastid tRNA genes encode a C at the 39 end (Mayer et al, 2000;Tomita et al, 1996). Aquifex aeolicus, Deinococcus radiodurans, some cyanobacteria and recently Bacillus halodurans, Bacillus clausii and Geobacter sulfurreducens have been found to contain separate enzymes for the addition of A and C residues to tRNA in vivo (Bralley et al, 2005(Bralley et al, , 2009Neuenfeldt et al, 2008;Seth et al, 2002;Tomita & Weiner, 2001. In Streptomyces coelicolor less than a third of the tRNA genes encode the CCA end and the product of SCO3896, the S. coelicolor CCase, is essential in this process (Bralley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In organelles, the tRNA nucleotidyltransferase only has to add two nucleotides, C and A, to the 39 end because a high number of plastid tRNA genes encode a C at the 39 end (Mayer et al, 2000;Tomita et al, 1996). Aquifex aeolicus, Deinococcus radiodurans, some cyanobacteria and recently Bacillus halodurans, Bacillus clausii and Geobacter sulfurreducens have been found to contain separate enzymes for the addition of A and C residues to tRNA in vivo (Bralley et al, 2005(Bralley et al, , 2009Neuenfeldt et al, 2008;Seth et al, 2002;Tomita & Weiner, 2001. In Streptomyces coelicolor less than a third of the tRNA genes encode the CCA end and the product of SCO3896, the S. coelicolor CCase, is essential in this process (Bralley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In some organisms a single CCase modifies the 39 end of damaged or immature tRNAs in a template-independent manner. Interestingly, it has been shown that in Aquifex aeolicus (Tomita & Weiner, 2001), Synechocystis sp., Deinococcus radiodurans (Tomita & Weiner, 2001), Bacillus halodurans (Bralley et al, 2005), Bacillus clausii (Neuenfeldt et al, 2008) and Geobacter sulfurreducens (Bralley et al, 2009) there are two enzymes, one of which adds the CC dinucleotide and one that adds the terminal A. In B. subtilis there is only a single gene coding for CCase (Raynal et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas such CCA-adding enzymes are found in most organisms, several bacteria like Aquifex aeolicus, Synechocystis species, Deinococcus radiodurans, Bacillus halodurans, Geobacter sulfurreducens, and Thermus thermophilus carry two closely related class II enzymes with partial activities (11)(12)(13)(14)(15). Here, one enzyme adds two C residues to the tRNA (CC-adding enzyme), and the second nucleotidyltransferase incorporates the terminal A (A-adding enzyme).…”
mentioning
confidence: 99%
“…Interestingly, these enzymes do not synthesize the complete CCA-end, but show a restricted activity. One enzyme adds exclusively two C residues to the tRNA primer, while the second one incorporates the terminal A. Consequently, these enzymes are called CC-and A-adding enzymes, respectively [52,[72][73][74][75]. The collaboration of both activities ensures a complete and efficient CCA synthesis.…”
Section: Closely Related Class II Nucleotidyltransferasesmentioning
confidence: 99%